2012
DOI: 10.1073/pnas.1212297109
|View full text |Cite
|
Sign up to set email alerts
|

Mineral dust photochemistry induces nucleation events in the presence of SO2

Abstract: Large quantities of mineral dust particles are frequently ejected into the atmosphere through the action of wind. The surface of dust particles acts as a sink for many gases, such as sulfur dioxide. It is well known that under most conditions, sulfur dioxide reacts on dust particle surfaces, leading to the production of sulfate ions. In this report, for specific atmospheric conditions, we provide evidence for an alternate pathway in which a series of reactions under solar UV light produces first gaseous sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
135
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(149 citation statements)
references
References 38 publications
(33 reference statements)
12
135
2
Order By: Relevance
“…Coagulation might be also invoked, but in this case, photochemistry would not be implied, in contradiction with Dupart et al's laboratory experiments [10]. As a result, our numerical simulation and lidar experiments provide strong arguments in favor of the remote lidar observation of a nucleation event promoted by dust particles.…”
Section: Lidar Observation Of a Nucleation Eventcontrasting
confidence: 39%
See 1 more Smart Citation
“…Coagulation might be also invoked, but in this case, photochemistry would not be implied, in contradiction with Dupart et al's laboratory experiments [10]. As a result, our numerical simulation and lidar experiments provide strong arguments in favor of the remote lidar observation of a nucleation event promoted by dust particles.…”
Section: Lidar Observation Of a Nucleation Eventcontrasting
confidence: 39%
“…Starting from an observed NPF-event promoted by desert dust particles [10], we numerically simulated the corresponding lidar particles backscattering coefficient βNPF, by applying the Mie theory to freshly nucleated sulfuric acid particles and the T-matrix numerical code [9] for non-spherical desert dust particles. We hence retrieved the optical requirement for detecting such a nucleation event (NPF-event) promoted by desert dust particles, for which the lidar backscattering coefficient βNPF is equal to 0.7 Mm -…”
Section: Methodology For Remotely Sensing a Npfevent With A Lidar Bacmentioning
confidence: 99%
“…10e). This layer can be possibly linked to the photochemically induced nucleation which may occur in the presence of dust and SO 2 as hypothesised in a recent study by Dupart et al (2012) and observed by Nie et al (2014).…”
Section: Layers With Enhanced Aitken-mode Particle Numbersmentioning
confidence: 95%
“…Instead, we used 7-day air mass back trajectories to identify the potential source of the nonspherical particles present at the remote site. Otherwise, we already published in Dupart et al (2012) on the combined use of our lidar depolarization experiment with laboratory chemical studies.…”
Section: G David Et Al: Retrieving Simulated Volcanic Desert Dust mentioning
confidence: 99%
“…Quantifying their effect is a challenging task, in part due to the complexity of these atmospheric particles, which present a wide range of sizes, shapes and chemical compositions with interconnected distributions, as we recently published in a comprehensive study (Dupart et al, 2012). Nonspherical particles are particularly challenging because there is no generic, exact light-scattering theory for such particles (Mishchenko et al, 2000;).…”
Section: Introductionmentioning
confidence: 99%